Development of Indonesian Language Learning Module Based on the Think Talk Write Model Assisted by Digital Media on Procedural Text Materials - D. Wulan Azzahra; Muhammad Akhir; Aliem Bahri (International Journal Labs, 2026)
This study aims to analyze the transformation of the writing process in producing complex procedural texts through the implementation of the Think Talk Write (TTW) model assisted by digital media among eleventh-grade students. The research employed a qualitative approach with a case study design to explore in depth the cognitive, social, and pedagogical dynamics occurring during the learning process. The participants consisted of one Indonesian language teacher and 50 eleventh grade students at UPTD SMPN 17 Marusu. Data were collected through participatory observation conducted over four instructional meetings, semi-structured interviews with the teacher and ten selected students, and document analysis of students’ writing before and after the implementation of the TTW model. Data were analyzed interactively through data reduction, data display, and conclusion drawing, while credibility was ensured through technique triangulation, source triangulation, and member checking. The findings indicate that the implementation of TTW assisted by digital media transformed writing instruction from a product-oriented approach into a process oriented one. The think stage functioned as an initial cognitive structuring phase to organize ideas, the talk stage facilitated social construction of meaning through collaborative discussion, and the write stage served as a consolidation process resulting in more coherent and systematically structured texts. Digital media acted as pedagogical scaffolding that supported text visualization, clarified procedural components, and strengthened textual coherence. These findings highlight that integrating TTW with digital media effectively enhances productive literacy through a process based pedagogical design.